Timing of Appendectomy and Postoperative Outcomes in Adult Acute Appendicitis: Systematic Review and Meta-Analysis - Alvian Dwisakti Kurniato (International Journal Of Health Science, 2026)
The optimal timing of appendectomy for acute appendicitis in adults remains debated. Advances in imaging and perioperative care have questioned the necessity of immediate surgery. This systematic review and meta-analysis evaluated whether moderate, in-hospital delays in appendectomy impact rates of postoperative complications or surgical site infection (SSI). A systematic search of PubMed, Embase, Scopus, and Web of Science through July 2025 identified randomized trials and cohort studies comparing early (≤6–8 hours) versus delayed (>6–12 hours) appendectomy in adults. Primary outcomes were composite postoperative complications and SSI. Random-effects models were used to pool risk ratios (RR) and 95% confidence intervals (CI). Five studies (over 600,000 adults) were included. Meta-analysis demonstrated no significant difference in composite complications between early and delayed appendectomy (RR 1.07, 95% CI: 0.62–1.85, p=0.81). Similarly, the risk of SSI was not different between groups (RR 1.16, 95% CI: 0.49–2.73, p=0.74). Heterogeneity was moderate for both outcomes. Secondary endpoints, including readmission, mortality, and length of stay, also showed no clinically meaningful differences by surgical timing. Only prolonged delays beyond 24-48 hours were associated with increased risk in select cohorts. For clinically stable adults with acute appendicitis, a short in-hospital delay in appendectomy typically up to 12 or 24 hours does not increase the risk of postoperative complications or surgical site infection. Flexible scheduling is safe when accompanied by prompt diagnosis and antibiotics, while prolonged or unplanned delays should be avoided.